COMPARATIVE ANALYSIS OF ATTITUDES TOWARDS THE SOCIOPOLITICAL SITUATION IN THE CHECHEN REPUBLIC (BASED ON SOCIOLOGICAL DATA) - BETILMERZAEVA, Maret; DZUTSEV, Hasan; -Emi SHAMSUEV, Magomed; SALGIRIEV, Ali (CENTRAL ASIA AND THE CAUCASUS, 2018)
The subject of analysis is the transformation of attitudes towards the sociopolitical situation in the Chechen society. The analysis is based on the data obtained through sociological surveys conducted by the North Ossetia Center for Social Research of the Institute of Socio-Political Research of the Russian Academy of Sciences and the Department of Sociological Studies of the North Ossetia Institute of Humanities and Social Research of the Vladikavkaz Center of the Russian Academy of Sciences and the Government of the Republic of North Ossetia-Alania in May-June 2003, as well as through joint research conducted by the North Ossetia Center for Social Research and the Department of Philosophy, Political Science and Sociology of the Chechen State Pedagogical University in May-June 2017.